Fermentation: improvement of pharmacological effects and applications of botanical drugs - Luo, Xinxin; Dong, Mosi; Liu, Juntong; Guo, Naifei; Li, Jing; Shi, Yan; Yang, Yufeng (Frontiers in Pharmacology, 2024)
Fermentation is an important concoction technique for botanical drugs. Fermentation transforms and enhances the active ingredients of botanical drugs through specific microbiological processes, ultimately affecting their pharmacological effects. This review explores the use of fermented botanical drugs in areas such as anti-tumor, hypolipidemic, antioxidant, antimicrobial, cosmetology, and intestinal flora regulation. It elucidates the potential pharmacological mechanisms and discusses the benefits of fermentation technology for botanical drugs, including reducing toxic side effects, enhancing drug efficacy, and creating new active ingredients. This article also discussesdelves into the common strains and factors influencing the fermentation process, which are crucial for the successful transformation and enhancement of these drugs. Taken together, this study aimed to provide a reference point for further research and wider applications of botanical drug fermentation technology.